EVALUASI MUTU SABUN PADAT TRANSPARAN DARI MINYAK GORENG BEKAS DENGAN PENAMBAHAN SLS (Sodium Lauryl Sulfate) DAN SUKROSA - Hardian, Khairil; Ali, Akhyar; ', Yusmarini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aims were to obtain the best concentration of sodium lauryl sulfate and sucrose and to know the characteristics consumer acceptance of transparent soap from purified used cooking oil. This research used completely randomized design (CRD) with 17 treatments and three replications.Observations of the purified used cooking oil were water content, free fatty acids, saponification number and descriptive organoleptic test. Meanwhile, the observations of transparent soap includes moisture content, free fatty acids, saponification number, pH, foam test, irritation test and organoleptic tests. The results showed that best formulation of transparent soap was1,5%sodium lauryl sulfateand 15,5% sucrose with water content 4,46%, free fatty acid not detected, the volume of foam is 166,49 cm3, pH 9,8, hardness test 0,37 cm/second and no cause irritation.   Keyword: cooking oil, transparent solid soap, sodium lauryl sulfate, sucrose.